(untitled) (Revista Electrónica REDINE, 2025)
The problem of mass tourism, which has generated negative impacts and, consequently, neglected the qualitative dimensions of the traveler experience. The overall purpose of the study was to examine the elements of the transpersonal paradigm relevant to the design of agroecological tourism routes and trails, with the goal of reconnecting human beings with nature and their own consciousness. To achieve this, a qualitative-interpretative approach was implemented, supported by the phenomenological-hermeneutic method, and data collection techniques such as in-depth interviews and self-observation were employed. The main findings were that the design of these experiences must integrate ancestral knowledge, generate an emotional and sensorial connection, and promote education for transformation through rituals and reflective practices. Finally, the study concludes by suggesting that applying this transpersonal model transforms tourism into a tool for personal growth, and recommends that tour planners and guides use this framework to create offerings that are not only commercial but also promote sustainability and well-being.